2018
DOI: 10.4103/joc.joc_162_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papilloma virus types in Turkish and Albanian women

Abstract: Background:Human papilloma virus (HPV) infection is the major etiologic agent of cervical carcinoma. The aim of this study was to determine the prevalence of HPV infection and genotype distribution in cervical swabs from 2,234 Turkish and 357 Albanian women with similar lifestyles from two different countries.Materials and Methods:HPV detection and typing were performed by type specific multiplex fluorescent PCR and fragments were directly genotyped by high resolution fluorescence capillary electrophoresis.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…From the 2,777 positive samples, single and multiple HPV genotypes, which we have started to see more recently, were found to be 46%, and 54%, respectively (Table 2), and these values were (0.3-0.8%) less common (Chelimo et al, 2013;Rob et al, 2017;Haeggblom et al, 2019;Broomall et al, 2010;Karlsen et al, 1994;Anderson LA et al, 2016;Coutlée et al, 2011;Dunne et al, 2007;Tjalma et al 2013). There were some studies supporting and also compatible with the results of our study from Turkey (Cilingir et al, 2013;Colakoglu et al, Duran et al, 2017;Hancer et al, 2018). Other studies from Turkey showed a high rate of multiple HPV infections such as 23.6% and 17.8% (Yuce et al, 2012;Eroglu et al, 2011) for multiple-genotype infections.…”
Section: Discussionsupporting
confidence: 87%
“…From the 2,777 positive samples, single and multiple HPV genotypes, which we have started to see more recently, were found to be 46%, and 54%, respectively (Table 2), and these values were (0.3-0.8%) less common (Chelimo et al, 2013;Rob et al, 2017;Haeggblom et al, 2019;Broomall et al, 2010;Karlsen et al, 1994;Anderson LA et al, 2016;Coutlée et al, 2011;Dunne et al, 2007;Tjalma et al 2013). There were some studies supporting and also compatible with the results of our study from Turkey (Cilingir et al, 2013;Colakoglu et al, Duran et al, 2017;Hancer et al, 2018). Other studies from Turkey showed a high rate of multiple HPV infections such as 23.6% and 17.8% (Yuce et al, 2012;Eroglu et al, 2011) for multiple-genotype infections.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of HR-HPV was reported to be 33.5%, 36.3%, 8.5%, 10.07%, 23.9%, and 2.79% in their studies, respectively (Aydogan et al, 2018, Alacam et al, 2021, Akcali et al, 2013, Bayram et al, 2015, Eroglu and Asgin 2020, Kulhan et al, 2017. In a study conducted on 2234 Turkish women, HPV positivity was found 38.05%, and the most common type was HPV 16 (Hancer et al, 2018). Overall, HPV-DNA positivity in Italy was identified in 35.9% of the women (Piana et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In Turkish and Albanian women, a study showed that HPV-16 and HPV-6 are the most common HPV genotypes. The other common types are HPV-18 and 39 for Albanian and Turkish women, respectively (Hancer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%